Seasonal Changes in the Occurrence of Listeria Monocytogenes in Duhok Province - Al-Brefkani, Azad M. T.; Mammani, Ismaeil M. A. (Science Journal of University of Zakho, 2019)
Listeria monocytogenes are Gram-positive bacilli cause listeriosis, associated with high rates of hospitalization and mortality. A total of 1362 samples were investigated included 647 clinical samples and 715 from food. This study investigated the differences in the seasonal occurrence of L. monocytogenes in Kurdistan region-Iraq. L. monocytogeneswas found in 48 samples (3.52%) out of 1362 samples. There were 7/642(1.09%) human clinical samples diagnosed with cold and moderate weather (November, December 2016, and January, February, April 2017). While 41/715(5.73%) of L. monocytogenesisolates were found among food samples, meat samples (n=37) and dairy samples (n=4). A total of 37/476 (7.77%) of the L. monocytogenes isolates in meat samplesweredetected during warm weather (from July through October 2016). In addition, L. monocytogenesin dairy products was found to be by 4/239 (1.68%), were isolated during the moderate season (October, November 2016, and April, May 2017). The study found that the incidence of meat contamination by L. monocytogenesincrease significantly during the warm season in comparison with other seasons. Furthermore, the cases of human Listeriosis caused correlated well with the seasonal levels of L. monocytogenesfound in dairy products. A statistically significant difference in the occurrence of L. monocytogenesisolates and seasons were identified in this study (P value= <0.05).